Determinant Factors of Type 2 Diabetes Mellitus of Visitors in the Integrated Guidance Posts of Jambi’s Kenali Besar Community Health Center - Vinna Juniarti Fatimah; Rd. Halim; Hendra Dhermawan Sitanggang; Evy Wisudariani (East Asian Journal of Multidisciplinary Research, 2022)
The study aims to discover the proportion and determinants of type-2 DM cases in the Integrated Guidance Posts of Kenali Besar Community Health Center in 2019. The study was a quantitative analysis with cross sectional design, the sample amounted to 278  ≥ 15 years old individuals. Study results indicated that 21.9% visitors of Integrated Guidance Posts suffered from type-2 diabetes mellitus, 18% with low education, 21.2% with family history of DM, 26.6% were smoking, 47.1% fell in the obese category of BMI, 55.8% were lacking physical activities, 23.7% with hypertension, and 64.4% fell in the central obesity category. Family history of DM, lack of physical activities, and hypertension were correlated with type-2DM cases in visitors of the Integrated Guidance Posts of Kenali Besar Community Health Center’s.